Refractory IgD Multiple Myeloma Treated with Daratumumab: A Case Report and Literature Review - Muhammad Husnain; Sandra Kurtin; Nikki Barkett; Irbaz bin Riaz; Amit Agarwal (Case Reports in Oncological Medicine)
Patients with relapsed and refractory multiple myeloma have poor prognosis. A recent analysis of patients with relapsed and refractory multiple myeloma who were refractory to both proteasome inhibitors and immunomodulatory drugs showed the median overall survival of 9 months only. Daratumumab is the first-in-class human monoclonal antibody against CD38 cells which was studied in phase I/II trials for treatment of these patients with relapsed refractory multiple myeloma. It showed an overall response rate of 36% and a median overall survival (OS) of 17 months in these patients. We report a case of 40-year-old man with immunoglobulin D (IgD) multiple myeloma whose disease was refractory to at least 5 different chemotherapy regimens including proteasome inhibitors and immunomodulatory drugs. The clinical studies assessing daratumumab did not include any patients with IgD myeloma which is a rare form of multiple myeloma and to our knowledge is the first study reporting use of daratumumab in IgD myeloma.